Mercury pollution in water, soil, and biota induced by artisanal gold mining: A case study from Ananea District, Puno, Peru - Huisa-Mamani, Fidel; Arizaca-Avalos, Americo; Llanque-Maquera, Oscar Eloy (Brawijaya University, 2025)
Artisanal and small-scale gold mining (ASGM) significantly contributes to global mercury pollution, posing serious environmental and health risks. This study assessed mercury contamination in the Ananea District, heavily impacted by ASGM activities. Mercury levels were measured in water, soil, and plant tissues using a Direct Mercury Analyzer (DMA-80). Results showed water mercury concentrations ranging from 0.1169 mg/kg to 1.54 mg/kg, far exceeding the World Health Organization's safe limit of 0.001 mg/kg. Soil samples contained mercury levels between 0.0909 mg/kg and 22.49 mg/kg, surpassing typical uncontaminated soil levels. Plant tissues had mercury concentrations from 0.0909 mg/kg to 7.7467 mg/kg, indicating potential entry into the food chain. Elevated mercury levels closely correlate with proximity to mining and processing sites, highlighting ASGM's direct environmental impact. These findings align with global patterns observed in other ASGM regions. The study underscores the urgent need for mitigation strategies, including stronger regulations, promotion of mercury-free technologies, and community engagement to reduce mercury emissions and protect public health.